History and Religion in the Modern Age - Fasolt, Constantin (History and theory, 2006)
This essay seeks to clarify the relationship between history and religion in the modern age. It proceeds in three steps. First, it draws attention to the radical asymmetry between first-person and third-person statements that Wittgenstein's Philosophical Investigations rescued from the metaphysical exile to which it had been condemned by Descartes's definition of the self as a thing. Second, it argues that religion is designed to alleviate the peculiarly human kind of suffering arising from this asymmetry. Third, it maintains that history relies on the same means as religion in order to achieve the same results. The turn to historical evidence performed by historians and their readers is more than just a path to knowledge. It is a religious ritual designed to make participants at home in their natural and social environments. Quite like the ritual representation of the death and resurrection of Christ in the Mass, the historical representation of the past underwrites the faith in human liberty and the hope in redemption from suffering. It helps human beings to find their bearings in the modern age without having to go to pre-industrial churches and pray in old agrarian ways. History does not conflict with the historical religions merely because it reveals them to have been founded on beliefs that cannot be supported by the evidence. History conflicts with the historical religions because it is a rival religion.